Genitourinary symptoms and quality of life of women with breast cancer undergoing chemotherapy - Aniele Tomadon; Jaqueline Lemos de Oliveira; Isabella Queren de Oliveira; Thais de Oliveira Gozzo (Universidade de São Paulo, 2023)
ABSTRACT This study aimed to compare genitourinary symptoms and quality of life in women with breast cancer before and after chemotherapy treatment. This is a prospective and analytical study carried out with 60 women treated at a hospital in the state of Paraná. Sociodemographic data, menopausal status, climacteric symptoms, quality of life, and pelvic floor strength and resistance were collected. Descriptive statistics, t-tests, Shapiro-Wilk, Cochran, Factorial Analysis of Variance for Repeated Measures and Fishers least significance difference were used for data analysis. Participants suffered genitourinary alterations, such as reduced strength and resistance of the pelvic floor muscles, urinary incontinence and vulvovaginal atrophy, regardless of the evaluated factors (type of chemotherapy, parity, and menopausal status). Therefore, greater attention and discussion by multidisciplinary health teams is necessary, as these symptoms can be reduced and managed if recognized early.